The effectiveness of organized offenses in high-level basketball - Tsiotras, D.; Mexas, K.; Garefis, A.; Tsitskaris, G. (Pre-olympic Congress 2004. Thessaloniki, Grécia. de 6 a 11 de Agosto de 2004, 2004)
Offense is divided into organized moves and fast breaks. The offensive organized moves consist about 85% of the total game1. One of the major problems is to define whether an offense is successful or not. Considering the quality of shots and the effectiveness of offenses, many opinions have been expressed. The purpose of the present study was to evaluate the effectiveness of Organized Offenses (O.O.), based on the circumstances (position achieved by the shooter-level of defensive pressure) under which the shot was taken and not on the final result (basket or no basket), in relation to some variables (shooting area, shooting side, player shooting and kind of defense). Methods The sample consisted of 50 high-level basketball games (25 Men's National Teams games from the European Championship in 2001 and 25 games from the First Division of Greek National League in 2001-2002). The scouting software for individual and team sports called SportScout was used for the analysis of the situations. The chi square test (p < 0.05) was used for statistical analysis. Results Overall, 54,5% of O.O were successful. Positions from which shots were eventually made, were as follows: 44% of O.O. ended up in the 3?? area and their effectiveness was 64,7%, 23% ended up in the 2 point area with 47,9% effectiveness and 33% ended up in the 3 point area with 48,4% effectiveness (x2 =407,295 p<0.05). In terms of shooting side, no significant differences were found. Concerning players, guards made 59% of the total attempts with 54,2% success rate and the remaining 41% was made by centers with 66,2% effectiveness (x2 =168,282 p<0.05). Finally, mtm defense was the most common (91%) and the success rate against it was 59,3%, zone defense accounted for 8%, success rate against it 56,8%; pressing was only used in 1% of instances and offenses were successful against it 52% of the time (x2 =61546,242 p<0.05). Discussion/ Conclusions The results of this study led to the conclusions that most shots are taken under good circumstances and the 3¨ area should be the preferred zone for shooting, yielding the highest success rate. In contrast, the shooting side is not of significance. Even though guards ended up making more shots, the centers were more efficient. Finally, the study showed mtm defense is by far the most common defense used in modern basketball.